The Architecture of Construction - Rosamund Diamond (Joelho)
The place of technical discourse in studio projects has been much debated.  The studio is the primary location to engage requisite construction knowledge creatively, in which assumptions about materials  could be transformed into tangible investigations with the skill and freedom to reinvent and invent. The paper will investigate the relationship of the craftsmanship of familiar construction methods to a broader context of fabrication and new material possibilities, in order to discuss how construction technique could be drawn into the conceptual centre of design studio projects. How the action of challenging construction conventions with the wide range of available technical advances could converse with the specificity of construction to its local conditions of building and place. Using some case studies, it will propose the value of construction to explore the broader conditions of architecture including its physical and critical topographies. Construction teaching in the studio will be considered in terms of its interrogation and description, as the basis for a discourse, using previous studio experiments. How can construction be developed in the studio so that it is embedded in the conceptual  development of student projects? How can studio construction investigations develop connections to place? In what ways can construction knowledge enable innovation without resisting the value of traditional material culture?